Development and validation of bioanalytical method for the detection of gliclazide in human plasma - Alaama, Mohamed; Helal Uddin, A.B.M.; Izat, I'zma; Kamarbashrudin, Siti Khadijah Rose (2016)
A robust High Performance Liquid Chromatography Diod Array Detection (HPLC- DAD) method was developed for the detection of gliclazide in human plasma. Liquid liquid extraction method was used as a sample preparation for HPLC analysis. The separation was carried out on Agilent Zorbax Reversed Phase C-18 column (150 x 4.6 mm, 5µ m) with PDA detection at 236 nm. with an isocratic elution (1 mL/min) at 30°C column temperature. The mobile phases used consisted of acetonitrile: 0.3% triethylamine buffer (pH=3.0 adjusted with H3PO4 85%) 57:43 v/v. Then, 10 µL aliquot samples were injected onto chromatographic system. The results showed that the retention time for the gliclazide and the internal standard, glibenclamide were 3.8 and 4.8 respectively. The method was linear over the range of 10 – 5000 ppb with R2 of 0.9971. The recoveries of the developed methods for gliclazide were found to be between 84.9% and 104.0%, while for the glibenclamide were found to be between 100.0% and 112.0%. The stability analysis showed that gliclazide is stable for at least 3 months but glibenclamide is degraded for about 2 months when stored at -20 ?. For conclusion, the develop method is suitable and reliable for the detection of gliclazide in human plasma.